Central Nervous System (CNS) T-Cell Lymphoma as the Presenting Manifestation of Late-Onset Combined Immunodeficiency - Jeffrey, Anthony; Coyle, Luke A.; Samaranayake, Dishan; Boyle, Therese; Drummond, James; Fernando, Suran L. (Case Reports in Hematology, 2023)
Late-onset combined immunodeficiency (LOCID), considered now a subset of common variable immunodeficiency (CVID) disorders, is characterized by a predominantly T-cell immune defect. LOCID has a distinct phenotype from CVID with a greater risk of lymphoproliferative complications. As compared to the CVID cohort, LOCID patients also have increased rates of splenomegaly and granulomatous disease. We report a case of central nervous system (CNS) T-cell lymphoma in a 67-year-old male as the presenting manifestation of LOCID. The patient achieved a complete response to therapy after 4 cycles of MATRix (methotrexate, cytarabine, and thiotepa) and 2 cycles of ICE (etoposide, carboplatin, and ifosfamide) chemotherapy followed by CNS-directed autologous stem cell transplantation. Intravenous immunoglobulin replacement was commenced to address the underlying immunodeficiency. Pulmonary lesions consistent with a diagnosis of granulomatous and lymphocytic interstitial lung disease (GLILD) were identified as a second noninfectious complication of LOCID. The pulmonary lesions resolved after chemotherapy and immunoglobulin replacement. The patient remains well with no evidence of disease recurrence now more than 18 months after completion of therapy. This is the first reported case of T-cell lymphoma in an adult patient with LOCID. Further study is needed to elucidate the mechanisms of transformation of B- or T-cells to lymphoproliferation in primary immunodeficiency patients as well as research to inform evidence-based therapeutic strategies for this challenging cohort of patients.